LEGAL AND INSTITUTIONAL MECHANISMS FOR ENHANCING THE COMPETITIVENESS OF AGRO-INDUSTRIAL PRODUCTION IN REGIONS (World Economics and Finance Bulletin, 2026)
In the context of intensifying competition in the global economy, the efficiency and competitiveness of agro-industrial production are emerging as strategic factors for ensuring sustainable economic growth. Particularly for countries reliant on agriculture, the development of the agro-industrial complex plays a decisive role not only in ensuring food security but also in increasing export potential, generating employment, and reducing regional economic disparities
Keywords: Agro-industrial production; economic growth